Learning together for mental health: feasibility of measures to assess a whole-school mental health and wellbeing intervention in secondary schools - Oliver Lloyd-Houldey; Joanna Sturgess; Neisha Sundaram; Steven Hope; Semina Michalopoulou; Elizabeth Allen; Lee Hudson; Stephen Scott; Dasha Nicholls; Deborah Christie; Rosa Legood; Chris Bonell; et al. (Public Health Research)
Background Population mental health in young people worsened during and since the COVID-19 pandemic. School environments can play a key role in improving young people’s mental health. Learning Together for Mental Health is a whole-school intervention aiming to promote mental health and well-being among young people in secondary schools. Before progressing to a Phase III effectiveness evaluation of the intervention, it is critical to assess the feasibility of trial measures at baseline and follow-up. Objective To evaluate the feasibility of trial measures and procedures within a feasibility study of a whole-school intervention aiming to promote mental health and well-being among young people in secondary schools, including whether we met our progression criterion of survey response rates of 60% or more in two or more schools at baseline and follow-up. Design and methods We conducted a feasibility study which included assessment of the indicative primary and secondary outcomes measures and procedures to be used in a future Phase III trial. Setting and participants Setting for our feasibility study included five state, mixed-sex secondary schools in southern England (one of which dropped out after baselines and one of which replaced this). We recruited year-7 students to participate in the baseline survey and year-10 students to participate in the follow-up survey at 12-month follow-up. Baseline and follow-up participants were different groups, as the focus was assessing feasibility of measures for the age groups that would be surveyed at baseline and follow-up in a Phase III randomised controlled trial. Our study was not powered or designed to estimate intervention effects. Interventions As part of our feasibility study, all schools received the Learning Together for Mental Health intervention for one academic school year. Main outcome measures The indicative primary outcome measure trialled was the total difficulties score of the Strengths and Difficulties Questionnaire. Indicative secondary outcomes measures trialled were the: Warwick-Edinburgh Mental Well-being Scale; Short Moods and Feelings Questionnaire; Generalised Anxiety Disorder-7 scale; Eating Disorders Examination – Questionnaire Short, self-harm (single item from the Health Behaviour in School-aged Children study); bullying victimisation (Gatehouse Bullying Scale); cyberbullying (two items adapted from the Dose Adjustment for Normal Eating II questionnaire); substance use (National Health Service measure); and Beyond Blue School Climate Questionnaire. Results Trial measures and procedures were feasible to implement and were acceptable to year-7 and year-10 students, teachers and parents. At baseline, response rates ranged from 58% to 91% between schools. Only two students were opted out by parents, and no students opted out in advance. Students refusing consent on the day of survey was rare (7%). Twelve per cent of students were absent. The follow-up survey had an overall response rate of 66%, ranging from 44% to 91%. Only two students were opted out by parents, and three students opted out in advance. Overall, 12% opted out on the day. Twenty per cent of students were absent. Variation in response rate reflected specific problems at certain schools. Surveys took 40–45 minutes at baseline and 30 minutes at follow-up. The trial progression criterion concerning response rates was achieved, with three of four schools at baseline and two of four schools at follow-up having responses rates above 60%. Limitations Our study involved a small, purposive sample of schools and students which are not representative of those in England. Conclusions With some minor amendments, trial measures and procedures should be applied in a future Phase III effectiveness evaluation of the Learning Together for Mental Health intervention. Future work Survey response rates could be improved if baseline and follow-up surveys are not scheduled in the last weeks of term, on Fridays or near mock General Certificate of Secondary Education exams. Completion of some measures (such as Eating Disorders Examination – Questionnaire Short) among year-7 students may be improved if question wording is tailored to be age-appropriate. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Public Health Research programme as award number NIHR131594. Plain language summary Population mental health in young people worsened during and since the COVID-19 pandemic. School environments can play a key role in improving young people’s mental health. We looked at whether or not it is possible to collect questionnaire data from year-7 and year-10 students in secondary schools. This was done to see if it would be possible to do a larger study in future to evaluate a new school programme called Learning Together for Mental Health, aimed at promoting mental health among secondary-school students. At four state, mixed-sex, secondary schools in southern England, we recruited year-7 students (aged 11–12 years) to complete questionnaires before the programme (baseline) and year-10 students (aged 13–14 years) to do so after the programme (follow-up) 12 months later. This was to assess whether trial procedures and various measures of impact were possible. Measures focused on mental health, mental well-being, moods and feelings, anxiety, eating behaviour and disorders, self-harm, bullying, cyberbullying, consumption of alcohol and illegal drugs, and school belonging and engagement. We counted the proportion of students who chose to participate in the survey and how much of the questionnaire and each measure they completed. The proportion of students who chose to participate in the survey was more than six in ten in three out of four schools at baseline and two out of four schools at follow-up. We found survey measures and procedures were possible to implement and acceptable to students, teachers and parents. With some minor amendments, survey measures and procedures should be applied in a future larger study to evaluate the impact of Learning Together for Mental Health. Survey response rates could be improved if surveys are not scheduled in the last weeks of term, on Fridays or near mock General Certificate of Secondary Education exams.